Antifungal and phytotoxicity of wood vinegar from biomass waste against Fusarium oxysporum f. sp. cubense TR4 infecting banana plants - Anggrayni, Dilla; Purnama, Indra; Saidi, Noor Baity; Novianti, Fawzia; Baharum, Nadiya Akmal; Mutamima, Anisa; Razali, Nur Amirah Syazwani; Boukherroub, Rabah (Springer Nature, 2025)
Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4) infection poses a serious threat to banana cultivation, leading to significant economic losses due to the lack of effective and sustainable disease management strategies. Wood vinegar, derived from biomass waste, offers a potential eco-friendly alternative to chemical pesticides for disease control. This study evaluated the antifungal activity of wood vinegar from coconut shells and Acacia wood residues at different concentrations (1, 2, 4, 6, 8, and 10% v/v) against Foc TR4 in vitro using the poisoned food technique and assessed its phytotoxicity on banana plants. Our results showed that wood vinegar from both sources completely inhibited the growth of Foc TR4 in vitro at all concentrations tested. The phytotoxicity effects of the different types of wood vinegar on the banana plants were also evaluated using the same concentrations via foliar spray and soil-drenching techniques. Growth parameters, including plant height, stem diameter and leaf number, were recorded at 24, 31, and 39 days after transplanting (DAT). Treatments with lower concentrations (2% v/v) promoted the growth of the banana plants, while at higher concentrations, severe phytotoxicity symptoms such as leaf necrosis and yellowing were observed. These findings provide valuable insights into the potential use of biomass waste-based wood vinegar for controlling Fusarium wilt in bananas.